Coupled modeling of storm surge and coastal inundation: a case study in New York City during Hurricane Sandy - Jie Yin; Ning Lin; Dapeng Yu (2016)
In this paper we describe a new method of modeling coastal inundation arising from storm surge by coupling a widely used storm surge model (ADCIRC) and an urban flood inundation model (FloodMap). This is the first time the coupling of such models is implemented and tested using real events. The method offers a flexible and efficient procedure for applying detailed ADCIRC storm surge modeling results along the coastal boundary (with typical resolution of ∼100 m) to FloodMap for fine resolution inundation modeling (< 5 m). The coastal inundation during Hurricane Sandy was simulated at both the city (New York City) and sub-regional (lower Manhattan) scales with various resolutions. Results obtained from the ADCIRC and coupled ADCIRC -FloodMap simulations were compared with the recorded (High Water Marks) and derived (inundation extent based on the planar method) data from FEMA. At the city scale, coupled ADCIRC -FloodMap modeling demonstrates improved prediction over ADCIRC modeling alone for both the extent and depth of inundation. The advantage of the coupled model is further illustrated in the sub-regional modeling, using a mesh resolution of 3 m which is substantially finer than the inland mesh resolution used by ADCIRC (> 70 m). In further testing, we explored the effects of mesh resolution and roughness specification. Results agree with previous studies that fine resolution is essential for capturing intricate flow paths and connectivity in urban topography. While the specification of roughness is more challenging for urban environments, it may be empirically optimized. The successful coupling of ADCIRC and FloodMap models for fine-resolution coastal inundation modeling unlocks the potential for undertaking large numbers of probabilistically-based synthetic surge events for street-level risk analysis.